Revenue Management Strategies in Airline Industry: A Literature Review - Manalu, Haposan Vincentius; Demas Haryo Bismantoko; Oktaviana Putri; Kresna Adi Mahendra (Jurnal Sistem Teknik Industri, 2024)
The airline industry has rapidly evolved, fostering intense competition among companies. This competition drives airlines to formulate strategies for revenue maximization, giving rise to Revenue Management. This literature review spans the past 13 years, examining the development of Airline Revenue Management methods. By analyzing 22 journals with at least Q2 and SINTA 2 indexing, three primary scopes emerge: Quantity Decision, Pricing Decision, and Structural Decision. Airlines predominantly employ dynamic pricing and programming to optimize revenue by adapting to ongoing changes. The development trend in Airline Revenue Management indicates a shift towards faster and more accurate processing through increased integration with simulation and algorithm programming. This paper identifies the three main scopes involved in revenue management strategies and explores the diverse approaches airlines take to optimize income. Notably, dynamic pricing and programming remain prevalent methods, adapting to changing decision variables. The evolving landscape emphasizes integration with advanced technology for efficient processing. The study utilizes numerical and case studies to exemplify the ongoing development of Airline Revenue Management methods within this dynamic industry.